Space management practices in building maintenance management for public university student’s accommodation / Nurul Farah Nadia Mohd Ali and Mohd Fadzil Mat Yasin - Mohd Ali, Nurul Farah Nadia; Mat Yasin, Mohd Fadzil (2023)
This study involves the identification of space management for students in public universities, mainly focusing on accommodation in UiTM Seri Iskandar. The space management in several blocks and their facilities were assessed. Calculation for space capacity was also conducted. Data for this study was collected through analysing building plans for several blocks in the university. Data were analysed by calculating Space Capacity Index (Density) Score from the building’s plan. This study emphasised opportunities for improvement and offered space management practises to improve the living and learning environments in public university facilities.